Road transport energy consumption and vehicular emissions in Lagos, Nigeria - Monica Maduekwe; Uduak Akpan; Salisu Isihak (African Governance and Development Institute (AGDI), 2020)
The "Avoid", "Shift" and "Improve" (A-S-I) approach is an effective method for transforming an unsustainable transport system to a sustainable one. This study intends to examine the possible impact of the A-S-I policy measures in transforming the transportation system in Lagos - the most populous city and the commercial capital of Nigeria. The study employs the Long Range Energy Alternative Planning (LEAP) model to project future energy demand and greenhouse gas emissions to determine the most effective A-S-I option for the city. We construct a business-as-usual scenario for Lagos as well as sustainable road transport alternative policy scenarios. The results show that Lagos' biggest obstacle to achieving its emission reduction target is the presence of very old vehicles on its roads. Our analysis shows that emission reduction in the road transport sector in Lagos is sensitive to vehicle survivability rate (i.e. the fraction of vehicles of a certain age still driven). We conclude that unless the age limit of vehicles in Lagos reduces from 40 years to 22 years, vehicle growth rate from 5% to 2% and mileage by 2% per year from 2020- 2032, Lagos may not achieve the target 50% emission reduction by 2032.
Keywords: 330; Road transport; energy consumption; greenhouse gas emissions; LEAP; Lagos; Nigeria